Small molecule anion carriers facilitate lactate transport in model liposomes and cells - Daniel Alonso-Carrillo; Alain Arias-Betancur; Israel Carreira-Barral; Pere Fontova; Vanessa Soto-Cerrato; María García-Valverde; Ricardo Pérez-Tomás; Roberto Quesada (iScience, 2023)
Summary: An excessive production of lactate by cancer cells fosters tumor growth and metastasis. Therefore, targeting lactate metabolism and transport offers a new therapeutic strategy against cancer, based on dependency of some cancer cells for lactate as energy fuel or as oncogenic signal. Herein we present a family of anionophores based on the structure of click-tambjamines that have proved to be extremely active lactate carriers across phospholipid membranes. Compound 1, the most potent lactate transmembrane carrier, was studied in HeLa cells. The use of a monocarboxylate transporters (MCTs) inhibitor proved that 1 is an active lactate transporter in living cells, confirming the results obtained in phospholipid vesicles. Moreover, an additive effect of compound 1 with cisplatin was observed in HeLa cells. Identification of active lactate anionophores working in living cells opens up ways to exploit this class of compounds as molecular tools and drugs addressing dysregulated lactate metabolism.